2017
DOI: 10.15345/iojes.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of Critical Thinking Scale through Philosophical Inquiry for Children 5-6 Years Old

Abstract: Philosophy for children approach has been implemented in 50 different countries, and the materials of this approach have been translated into 20 different languages. Lipman (2003) describes this approach as a philosophy-based approach to encourage critical thinking in students. The purpose of this study is to develop the "Critical Thinking Scale through Philosophical Inquiry" for the children at 5 and 6 years in pre-school period and to conduct the validity and reliability studies. The study group consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…This study deployed a "Personal Information Form" to obtain demographic information regarding children and their families. To measure the effectiveness of the developed curriculum, "Critical Thinking Scale through Philosophical Inquiry for Children 5-6 Years Old (CTSPI)" developed by Karadağ, Yıldız Demirtaş and Yıldız (2017) and "Problem Solving Skills Scale for Children (PSSS)" developed by Oğuz and Köksal Akyol (2015) were used as pretest and post-test.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study deployed a "Personal Information Form" to obtain demographic information regarding children and their families. To measure the effectiveness of the developed curriculum, "Critical Thinking Scale through Philosophical Inquiry for Children 5-6 Years Old (CTSPI)" developed by Karadağ, Yıldız Demirtaş and Yıldız (2017) and "Problem Solving Skills Scale for Children (PSSS)" developed by Oğuz and Köksal Akyol (2015) were used as pretest and post-test.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Critical thinking scale through philosophical inquiry for children 5-6 years old (CTSPI): Being a 5-point Likert type ("Never", "Sometimes", "Rarely", "Often" and "Always"), the scale consisted of three sub-factors (Philosophical Inquiry, Language and Cognitive Skills and Formulating Question) and 38 items. Karadağ, Yıldız Demirtaş and Yıldız (2017) examined the implicit structure of the scale through exploratory factor analysis and model fit with confirmatory factor analysis to ensure the construct validity of the scale. The internal consistency coefficients of the scale were noted to be high (.974, .955, .983, .986).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Necatibey Faculty of Education, Electronic Journal of Science and Mathematics Education kitapları incelendiğinde, okul öncesi çocukların eleştirel düşünme becerilerinin genel olarak düşünme becerileri başlığı altında incelendiği görülmektedir (Akman & diğerleri, 2010;Arı & Öncü;2011;Kandır, Yaşar & Tuncer, 2011;Şen & diğerleri, 2011;Şahin & Ulutaş, 2014;Şahin & diğerleri, 2015;Yıldız, 2017). Diğer bir yandan, eleştirel düşünme becerilerini ayrı bir başlık altında ele alan kaynakların da yetersiz olduğu ve eleştirel düşünmenin hangi boyutlarının hangi etkinliklerle geliştirilebileceği konusunun ayrıntılı olarak ele alınmadığı dikkati çekmektedir.…”
Section: Necatibey Eğitim Fakültesi Elektronik Fen Ve Matematik Eğitimi Dergisiunclassified
“…Over the past decade, studies have shown that critical thinking can be taught to school kids (e.g. Florea & Hurjui, 2015;Marie-France & Mathieu, 2012;Nilson, Fetherston, McMurray, Fetherston, 2013;Qizi & Qizi, 2021) and even pre-school children (Karadağ, Demirtaş, & Yıldız, 2017).…”
Section: Introductionmentioning
confidence: 99%